Tips, Tricks, and Pearls for a Superior Patient and Surgeon Experience for Wide-awake Dupuytren Surgery - Natasha Barone, MDCM, MSc; Donald H. Lalonde, MD, MSc, FRCSC; Jean Paul Brutus, MD (Plastic and Reconstructive Surgery, Global Open, 2024)
Summary:. Fasciectomy for Dupuytren disease is a common procedure traditionally performed with a tourniquet under general or regional anesthesia. Since the year 2001, the wide-awake local anesthesia no tourniquet (WALANT) approach has been applied successfully to Dupuytren surgery, with current excellent surgeon and patient satisfaction. However, using WALANT for Dupuytren surgery may be intimidating for hand surgeons who want to begin using this method. The purpose of this article is to offer a series of tips and tricks the authors have learned after having performed hundreds of WALANT fasciectomies, to make this technique easier for surgeons and a more pleasurable experience for patients.